FASILITAS PENGOLAHAN DAUR ULANG SAMPAH DI TANAH MERAH JAKARTA DENGAN FASILITAS EDUKASI - Bimo Dwi Hannanto; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2022)
The problem of waste is a serious matter in Indonesia because the amount is already excessive. Most of the current waste is plastic waste that comes from households. Currently, Indonesia is an upper-middle class country, which means it is capable of becoming an independent industrial country. Previously, Indonesia had always imported waste as industrial raw material. It makes the waste problem even worse in Indonesia. Waste management in Indonesia is not managed sustainably. This has caused the Bantargebang TPA as a waste disposal site for DKI Jakarta to run out of land. Therefore, urban acupuncture is used as a method for selecting locations that have the most waste problems. The location of Tanah Merah in North Jakarta is the main focus, due to the degradation of the Tanah Merah TPS which makes the surrounding area unproductive. The existence of this problem gave the idea of ​​​​designing